# algebra 2

posted by .

If you were to use the substitution method to solve the following system, choose the new equation after the expression equivalent to x from the first equation is substituted into the second equation.

x + y = 2
3x + 2y = 9

• algebra 2 -

x + y = 2 Multiply both sides by 2

2 x + 2 y = 4

2 y = 4 - 2 x

3 x + 2 y = 9

3 x + 4 - 2 x = 9

x + 4 = 9

x = 9 - 4 = 5

x + y = 2

5 + y = 2

y = 2 - 5 = - 3

## Similar Questions

1. ### Substitution Method-Plz help

Use the Substitution method to solve the system of equations. x + y = -4 x - y = 2 solve for x in the second equation. x= y+2 Put that in for x in the first equation: x+y=-4 (y+2) + y = -4 solve for y. Then, x= y+2 i don't get it.How …
2. ### ALGEBRA 1!PLZ HELP!

Use the Substitution method to solve the system of equations. y - 2x = -5 3y - x = 5 Solve the first equation for y. y = 2x-5 Substitute that for y in the second equation and solve for x. Then use the value of x to substitute back …
3. ### correction of math

can someone correct this for me please. Directions: Solve the system by substitution. x + y = 12 y = 2x this is what i did: in the first equation i substituted y for what i have in the second equation so now it looks like this: x +2x …
4. ### subsitution method

Can some one show me how to use the Substitution method to solve the system of these equations. x + y = -4 x - y = 2 x + y = 10 y = x + 8 on the first set. Solve for either x or y in either equation, then put that value into the other …
5. ### Algebra

To solve the system of equations, which expression could be substituted for x into the first equation?
6. ### Algebra 2

If you were to use the substitution method to solve the following system, choose the new equation after the expression equivalent to x from the first equation is substituted into the second equation. x – 2y = 2 x + 3y = 17
7. ### algebra 2

to solve the system of equations which expression could be substituted for x into the first equation?
8. ### Algebra 1

What is an equation of a line perpendicular to the line with equation y = 1 - 3x a.y=-3x + 5 b. y=3x + 5 c.y=-1/3x + 5 d. y=1/3x + 5 To solve the linear system below, which substitution of unkowns is proper ?
9. ### Algebra II

If you were to use the substitution method to solve the following system, choose the new system of equations that would result if x was isolated in the third equation. 2x - 3y + z = -4 2x - 2y + z = -1 x - 2y + 3z = -6 5x + 7y = 6 …
10. ### Algebra

For the following system, if you isolated x in the first equation to use the Substitution Method, what expression would you substitute into the second equation?

More Similar Questions